Rheology of the sesame oil-in-water emulsions stabilized by cellulose nanofibers. (September 2019) - Lu, Yu; Qian, Xiaoli; Xie, Wenyuan; Zhang, Wenting; Huang, Jing; Wu, Defeng
Abstract: The sesame oil-in-water Pickering emulsions using cellulose nanofibers (CNF) as the emulsifier were prepared for the rheological study, aiming at establishing relationship between emulsion viscoelasticity and morphology. A droplet cluster structure forms in those systems due to multicomponent properties of sesame oil and fibrillar structure of CNF. Its deformation and relaxations result in weak strain overshoot behavior in large amplitude oscillatory shear (LAOS) flow, but not affect the scaling behavior of small amplitude oscillatory shear (SAOS) responses. The relaxation time scales can be evaluated by creep of emulsions. This structure can evolve during ramp shear flow, rearranged and oriented at the higher flow rates, which has evident influence on the thixotropic behavior of emulsions. The mechanisms of evolution and relaxations of droplet cluster structure are traced through rheo-optical way. This work presents some interesting results and paves a possible way to control morphology and viscoelasticity of edible Pickering emulsions. Graphical abstract: Image 1 Highlights: CNF can be used to stabilize edible sesame oil-in-water Pickering emulsions. Relaxations of droplet clusters lead to strain overshoot behavior during LAOS. SAOS flow shows scaling behavior regardless of W/O ratios and CNF loadings. Thixotropic properties depend on concentration and evolution of droplet clusters. Paving a way to control morphology and viscoelasticity of Pickering emulsions.